Listening to Antarctica: Cheryl E. Leonard’s eco-acoustic creative practice - Rachel Meyers; Carolyn Philpott (2021)
Listening to the more-than-human world has been a source of musical creativity for centuries, but what does it mean to listen and respond creatively to the world around us in the Anthropocene? This article contributes to a growing body of research on sonic representations of Antarctica, a place often viewed as a barometer of anthropogenic climate change. Although explorers and scientists have visited the icy continent for over a century, it is only in the past 25 years that composers and sound artists have had direct access to listen to the human and non-human sounds of Antarctica and capture them in creative works. Using composer Cheryl Leonard’s multimedia work Fluxes (2014) as a case study, this article investigates how Leonard’s eco-acoustic compositional practices reflect her listening experiences in Antarctica. We will highlight aspects of Leonard’s creative practice that contribute to her complex exploration of non-hierarchical relations between the human and non-human, and how she formulates non-dualistic relationships between nature, the human and technology in her imaginations of the natural world, including through her innovative employment of natural materials and her use of technology in the gathering of sounds and in live performance.